Juridical Study Determining the Implementation of the Corruption Eradication Article Based on Sema Number 7 of 2012 - Firman Harefa; Muhammad Yusuf Siregar; Wahyu Simon Tampubolon (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This research uses a normative legal research method which discusses changes in the provisions on the value of state financial losses in cases of criminal acts of corruption based on the Supreme Court Circular Letter (SEMA). SEMA Number 7 of 2012 states that state financial losses are above Rp. 100,000,000.00 can be subject to Article 2 paragraph (1) UUPTPK, while losses below that figure are subject to Article 3 UUPTPK. However, due to changes in currency values, SEMA Number 3 of 2018 changed the loss limit to IDR. 200,000,000.00. If the value of state losses is above Rp. 200,000,000.00, then Article 2 paragraph (1) UUPTPK applies, while losses are below or up to Rp. 200,000,000.00 applies to Article 3 UUPTPK. This change aims to provide legal certainty and make it easier for law enforcement officials to determine the articles that are suspected of committing criminal acts of corruption. Apart from that, this revision is an effort by the Supreme Court to eliminate the alleged practice of buying and selling articles in handling corruption cases. According to researchers, if there are no provisions for this change, the application of law in Indonesia will be ineffective because law functions to create order, justice and legal certainty in state life.